Changing patterns of the East Asian monsoon drive shifts in migration and abundance of a globally important rice pest. Issue 10 (27th February 2023) - Lv, Hua; Zhai, Meng‐Yuan; Zeng, Juan; Zhang, Yi‐Yang; Zhu, Feng; Shen, Hui‐Mei; Qiu, Kun; Gao, Bo‐Ya; Reynolds, Don R.; Chapman, Jason W.; Hu, Gao
Abstract: Numerous insects including pests and beneficial species undertake windborne migrations over hundreds of kilometers. In East Asia, climate‐induced changes in large‐scale atmospheric circulation systems are affecting wind‐fields and precipitation zones and these, in turn, are changing migration patterns. We examined the consequences in a serious rice pest, the brown planthopper (BPH, Nilaparvata lugens ) in East China. BPH cannot overwinter in temperate East Asia, and infestations there are initiated by several waves of windborne spring or summer migrants originating from tropical areas in Indochina. The East Asian summer monsoon, characterized by abundant rainfall and southerly winds, is of critical importance for these northward movements. We analyzed a 42‐year dataset of meteorological parameters and catches of BPH from a standardized network of 341 light‐traps in South and East China. We show that south of the Yangtze River during summer, southwesterly winds have weakened and rainfall increased, while the summer precipitation has decreased further north on the Jianghuai Plain. Together, these changes have resulted in shorter migratory journeys for BPH leaving South China. As a result, pest outbreaks of BPH in the key rice‐growing area of the Lower Yangtze River Valley (LYRV) have declined since 2001. We show that these changes to the East Asian summer monsoon weather parameters are driven by shifts in the position and intensity of the Western Pacific subtropical high (WPSH) system that have occurred during the last 20 years. As a result, the relationship between WPSH intensity and BPH immigration that was previously used to predict the size of the immigration to the LYRV has now broken down. Our results demonstrate that migration patterns of a serious rice pest have shifted in response to the climate‐induced changes in precipitation and wind pattern, with significant consequences for the population management of migratory pests. Abstract : In East Asia, climate‐induced changes in the Western Pacific subtropical high (WPSH) atmospheric circulation system are affecting wind‐fields and precipitation zones and these, in turn, are changing the migration pattern of brown planthopper (BPH) in eastern Asia. As a result, immigration levels of pest outbreaks of BPH in the key rice‐growing area of the Lower Yangtze River Valley (LYRV) have declined since 2001. Our results demonstrate that migration patterns of a serious rice pest have shifted in response to the climate‐induced changes in precipitation and wind pattern, with significant consequences for the population management of migratory pests.